Association of Myomectomy With Anti-Müllerian Hormone Levels and Ovarian Reserve. Issue 6 (2nd December 2022) - Aharon, Devora; Sekhon, Lucky; Getrajdman, Chloe; Naert, Mackenzie; Hanley, William; Kerr, Ahmad; Ghofranian, Atoosa; Hernandez-Nieto, Carlos; Lee, Joseph A.; Copperman, Alan; Ascher-Walsh, Charles
Abstract : Myomectomy is associated with a short-term decline in serum anti-müllerian hormone levels; however, no long-term change in ovarian reserve, as measured by anti-müllerian hormone levels, is observed, regardless of route of surgery. Abstract : OBJECTIVE: To assess whether open and minimally invasive myomectomy are associated with changes in postoperative ovarian reserve as measured by serum anti-müllerian hormone (AMH) level. METHODS: This prospective cohort study included patients who were undergoing open abdominal myomectomy that used a tourniquet or minimally invasive (robot-assisted or laparoscopic) myomectomy that used vasopressin. Serum AMH levels were collected before the procedure and at 2 weeks, 3 months, and 6 months after surgery. The mean change in AMH level at each postsurgery timepoint was compared with baseline. The effect of surgical route on the change in AMH level at each timepoint was assessed by using multivariable linear regression. A subanalysis evaluated postoperative changes in AMH levels among the open myomectomy and minimally invasive myomectomy groups individually. RESULTS: The study included 111 patients (mean age 37.9±4.7 years), of whom 65 underwent open myomectomy and 46 underwent minimally invasive myomectomy. Eighty-seven patients contributed follow-up data. Serum AMH levels declined significantly at 2 weeks postsurgery (mean change −0.30 ng/mL, 95% CI −0.48 to −0.120 ng/mL, P =.002). No difference was observed at 3 months or 6 months postsurgery. On multiple linear regression, open myomectomy was significantly associated with a decline in AMH level at 2 weeks postsurgery (open myomectomy vs minimally invasive myomectomy: β=−0.63±0.22 ng/mL, P =.007) but not at 3 months or 6 months. Subanalysis revealed a significant decline in mean serum AMH levels in the open myomectomy group at 2 weeks (mean change −0.46 ng/mL, 95% CI −0.69 to −0.25 ng/mL, P <.001) postsurgery but not at three or 6 months. In the minimally invasive myomectomy group, no significant differences in mean AMH levels were detected between baseline and any postoperative timepoint. CONCLUSION: Myomectomy is associated with a transient decline in AMH levels in the immediate postoperative period, particularly after open surgery in which a tourniquet is used. Anti-müllerian hormone levels returned to baseline by 3 months after surgery, indicating that myomectomy is not associated with a long-term effect on ovarian reserve, even with the use of a tourniquet to decrease blood loss. FUNDING SOURCE: This study was funded in part by a Roche Diagnostics Investigator-Initiated Study Grant.